Efficient Access to All‐Carbon Quaternary and Tertiary α‐Functionalized Homoallyl‐type Aldehydes from Ketones. Issue 41 (1st September 2017) - Pace, Vittorio; Castoldi, Laura; Mazzeo, Eugenia; Rui, Marta; Langer, Thierry; Holzer, Wolfgang
Abstract: β, γ‐Unsaturated aldehydes with all‐carbon quaternary or tertiary α‐centers were rapidly assembled from ketones through a unique synthetic operation consisting of 1) C1 homologation, 2) Lewis acid mediated epoxide–aldehyde isomerization, and 3) electrophilic trapping. The synthetic equivalence of a vinyl oxirane and a β, γ‐unsaturated aldehyde is the key concept of this previously undisclosed tactic. Mechanistic studies and labeling experiments suggest that an aldehyde enolate is a crucial intermediate. The homologating carbenoid formation plays a critical role in determining the chemoselectivity. Abstract : Three in one : β, γ‐Unsaturated aldehydes with all‐carbon quaternary or tertiary α‐centers were rapidly assembled from ketones through a unique synthetic operation combining C1 homologation, Lewis acid mediated epoxide–aldehyde isomerization, and electrophilic trapping. Mechanistic studies and labeling experiments suggest that an aldehyde enolate is a crucial intermediate of this process.